Solvent-free hard coat resin composition and optical laminate including the same
Patent Information
- Application Number
- JP2023125221
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-01
AI Technical Summary
【0011】 本発明の樹脂組成物は、無溶剤型でありながら塗工外観が安定し、良好な耐擦傷性と共に優れた屈曲性を有するため、HCフィルム等に用いる無溶剤型のHC樹脂組成物として有用である。
Smart Images

Figure 2025021498000001 
Figure 2025021498000002 
Figure 2025021498000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a solvent-free hard coat resin composition that does not contain a diluting solvent, and an optical laminate using the same. [Background technology]
[0002] Acrylic photocurable resins are used in many fields to impart functionality to the surfaces of plastic films and plastic molded products. For example, hard coat (hereinafter referred to as HC) films, which are applied to PET (polyethylene terephthalate) films to impart high hardness, are used in large quantities as films for touch panels and molding films.
[0003] Such HC resin compositions generally tend to have high viscosity, and are often diluted with a solvent to improve coatability. However, such solvent-containing compositions have a large environmental impact because the solvent is evaporated after coating, and the drying oven consumes a large amount of energy. Furthermore, compared to solvent-based types, solventless types have a lower penetration and swelling effect on the easy-to-adhere layer formed to promote adhesion, and tend to have insufficient adhesion.
[0004] As a solventless HC curing composition that addresses these issues, for example, a composition containing a urethane (meth)acrylate structure with a specific structure, a polyfunctional compound, a monofunctional compound, a silicone compound, and a photoradical initiator has been proposed (Patent Document 1). By using such a solventless HC agent, the problems of the burden on the environment and energy loss during drying can be solved, but there are advantages and disadvantages to the various properties required for HC films, such as appearance, curability, and scratch resistance, and there are almost no compositions that can satisfy these physical properties in an averagely balanced manner, and there is room for improvement, especially in terms of flexibility. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] WO2009 / 050957 Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention provides an HC resin composition which is solvent-free and yet has a stable coating appearance, good scratch resistance and excellent flexibility, and an optical laminate having a cured layer thereof formed thereon. [Means for solving the problem]
[0007] In order to achieve the above object, the invention described in claim 1 provides a solventless hard coat resin composition comprising an alkylene oxide-modified polyfunctional (meth)acrylate (A), a vinyl ether group-containing (meth)acrylate (B), and a photopolymerization initiator (C), wherein the blending amount of (B) is 15 to 70% by weight based on the total solid content.
[0008] The invention described in claim 2 provides the solventless hard coat resin composition according to claim 1, characterized in that (A) contains a (meth)acrylate derivative selected from the group consisting of glycerin poly(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol poly(meth)acrylate.
[0009] The invention according to claim 3 provides the solventless hard coat resin composition according to claim 1, characterized in that (B) is a monofunctional (meth)acrylate containing one vinyl ether group in the molecule.
[0010] The invention according to claim 4 provides an optical layered body comprising a plastic substrate and a cured layer of the solventless hard coat resin composition according to any one of claims 1 to 3 formed on at least one surface of the plastic substrate. Effect of the Invention
[0011] INDUSTRIAL APPLICABILITY The resin composition of the present invention is a solvent-free type, yet has a stable coating appearance, good scratch resistance and excellent flexibility, and is therefore useful as a solvent-free HC resin composition for use in HC films and the like. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below.
[0013] The composition of the present invention is composed of an alkylene oxide-modified polyfunctional (meth)acrylate (A), a vinyl ether group-containing (meth)acrylate (B), and a photopolymerization initiator (C). In this specification, (meth)acrylate includes both acrylate and methacrylate. Solvent-free means that a solvent is not intentionally blended into the HC resin composition for the purpose of dilution, and does not mean that even volatile components contained in small amounts in each component of the HC resin composition are excluded, and the solvent content is 5% by weight or less, typically 1% by weight or less.
[0014] The alkylene oxide-modified polyfunctional (meth)acrylate (A) used in the present invention is a main component of the cured coating film, which has an alkylene oxide block structure in the skeleton. Since it is alkylene oxide-modified, it has low viscosity, and the reactive functional groups, acryloyl groups, can be kept at a certain distance from each other, so that the crosslinking density is not excessively high, and the internal stress and curing shrinkage remaining in the coating film can be reduced. Therefore, a good balance between the adhesion to the substrate and the coating film strength can be achieved, and as a result, a cured coating film that is also flexible can be formed.
[0015] Examples of alkylene oxide modifications include ethylene oxide (hereinafter referred to as EO) modifications, propylene oxide (hereinafter referred to as PO) modifications, and butylene oxide (hereinafter referred to as BO) modifications. The average number of alkylene oxide modifications is preferably 2 to 15, and more preferably 3 to 12. By making it 2 or more, improvement in scratch resistance and flexibility can be expected, and by making it 15 or less, it is easy to adjust the viscosity to an appropriate level.
[0016] Examples of the (A) include EO-modified glycerin poly(meth)acrylate, EO-modified diglycerin poly(meth)acrylate, EO-modified trimethylolpropane tri(meth)acrylate, EO-modified pentaerythritol poly(meth)acrylate, EO-modified dipentaerythritol poly(meth)acrylate, and their PO-modified and BO-modified products, and can be used alone or in combination of two or more. Among these, EO-modified products are preferred in terms of viscosity, curability, and availability. In addition, EO-modified diglycerin tetraacrylate (hereinafter referred to as DGTA), EO-modified dipentaerythritol hexaacrylate (hereinafter referred to as DPHA), and EO-modified trimethylolpropane triacrylate (hereinafter referred to as TMPTA) are particularly preferred in terms of a good balance between flexibility and scratch resistance.
[0017] The blending amount of the (A) is preferably 20 to 80% by weight, more preferably 25 to 70% by weight, and particularly preferably 35 to 60% by weight, based on the total solid content. By making it 20% by weight or more, sufficient flexibility and scratch resistance can be ensured, and by making it 80% by weight or less, sufficient coatability and stable appearance can be ensured.
[0018] The vinyl ether group-containing (meth)acrylate (B) used in the present invention is blended as a reactive diluent for diluting (A). It is a monomer having both a cationically polymerizable vinyl ether group having good dilutability without being inhibited by oxygen, and a (meth)acryloyl group having good compatibility and reactivity with (A), and can be represented, for example, by the following general formula (1). CH2=CR 1 -CO-(OCHR 2 CHR 3 )nO-CH=CHR 4 (1) (In the formula, R1 and R4 represent a hydrogen atom or a methyl group, R2 and R3 each independently represent a hydrogen atom or an organic residue, and n represents an integer of 2 or more.)
[0019] Examples of the (B) include 2-(2-vinyloxyethoxy)ethyl (meth)acrylate, 2-(2-vinyloxyisopropoxy)ethyl (meth)acrylate, 2-(2-vinyloxyethoxy)propyl (meth)acrylate, 2-(2-vinyloxyisopropoxy)propyl acrylate, 2-(2-vinyloxyethoxyethoxy)ethyl (meth)acrylate, etc., which can be used alone or in combination of two or more. Among these, 2-(2-vinyloxyethoxy)ethyl acrylate is particularly preferred, as it has low viscosity, high dilution ability, and excellent curing properties.
[0020] The blending amount of the (B) is 15 to 70% by weight, preferably 20 to 65% by weight, more preferably 25 to 60% by weight, and particularly preferably 30 to 55% by weight, based on the total solid content. If it is less than 15% by weight, the coatability may decrease and the appearance may not be stable, and if it exceeds 70% by weight, sufficient scratch resistance may not be ensured.
[0021] The photopolymerization initiator (C) used in the present invention generates radicals when irradiated with ultraviolet light or an electron beam, and the radicals trigger the polymerization reaction, and general-purpose photopolymerization initiators such as benzyl ketal, acetophenone, and phosphine oxide photopolymerization initiators can be used. By arbitrarily selecting the light absorption wavelength of the polymerization initiator, it is possible to impart curability over a wide wavelength range from the ultraviolet region to the visible light region. Specifically, the benzyl ketal type includes 2.2-dimethoxy-1.2-diphenylethan-1-one, the α-hydroxyacetophenone type includes 1-hydroxy-cyclohexyl-phenyl-ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propan-1-one, the α-aminoacetophenone type includes 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, and the acylphosphine oxide type includes 2.4.6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2.4.6-trimethylbenzoyl)-phenylphosphine oxide, which can be used alone or in combination of two or more. Among these, it is preferable to use an α-hydroxyphenone type which is less susceptible to yellowing, and more preferably 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propan-1-one which is less susceptible to polymerization inhibition by oxygen and has excellent surface curing properties.
[0022] The amount of (C) is preferably 0.5 to 10 parts by weight, more preferably 2 to 8 parts by weight, based on 100 parts by weight of the radical polymerizable component. By adding 0.5 parts by weight or more, sufficient curing properties are exhibited, and by adding 10 parts by weight or less, yellowing of the coating film and deterioration of storage stability can be prevented without excessive addition. Commercially available products include Omnirad127 (trade name: IGM Resins, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propan-1-one).
[0023] Furthermore, if necessary, additives such as reactive diluents, surface conditioners, light stabilizers, polymerization inhibitors, wetting agents, antioxidants, curing assistants, silane coupling agents, plasticizers, sensitizers, defoamers, flame retardants, inorganic fillers, organic fine particles, colorants such as pigments, dyes and colorants, antibacterial agents and antiviral agents can be used in combination with the present composition within a range that does not impair the performance.
[0024] The reactive diluent is blended for the purpose of reducing the viscosity of the composition and improving the curing property. It is preferable to use a multifunctional (meth)acrylate, since it has a low viscosity and excellent compatibility with (A) and (B). For example, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, diglycerin tetra(meth)acrylate are tetrafunctional, dipentaerythritol penta(meth)acrylate is pentafunctional, and dipentaerythritol hexa(meth)acrylate is hexafunctional, and these can be used alone or in combination of two or more kinds. Among these, DPHA is preferable, since it can improve the curing property and provide good scratch resistance.
[0025] The amount of the reactive diluent is preferably 25% by weight or less, more preferably 20% by weight or less, and particularly preferably 15% by weight or less, based on the total solid content. By making the amount 25% by weight or less, it is possible to improve the scratch resistance while ensuring sufficient flexibility.
[0026] The surface conditioner is blended for the purpose of improving the leveling property after coating and imparting antifouling (antifingerprint) and water repellency. In that it is not lost over time from the cured coating and its effect can be sustained for a long time, it is preferably a fluorine-based, silicone-based, or fluorine silicone-based agent having a reactive functional group that undergoes a polymerization reaction with (A) or (B).
[0027] Examples of plastic substrates to which the HC resin composition of the present invention is applied include triacetyl cellulose films, PET films, polyimide films, polyethylene naphthalate films, polyvinyl chloride films, polystyrene films, acrylic films, polycarbonate films, cycloolefin (co)polymer films, polyolefin films (PP, PE, etc.), and composite films thereof. Among these, biaxially oriented PET films are preferably used because of their good overall balance of price, processability, dimensional stability, etc.
[0028] The method for coating the HC resin composition of the present invention is not particularly limited, and for planar objects such as films and sheets, known coating methods such as spray coating, roll coating, die coating, air knife coating, blade coating, spin coating, reverse coating, gravure coating, wire bar, or gravure printing, screen printing, offset printing, inkjet printing, etc. can be used, and for objects that are not planar but have an uneven surface such as molded products, the spray coating method is useful. This method is also excellent as a method that can coat a wide area even on planar objects without large capital investment.
[0029] The coating thickness of the HC resin composition of the present invention is, for example, 0.5 μm to 50 μm when dry, but is not limited thereto. However, when coating a plastic substrate, the thickness is preferably 1 to 10 μm in order to prevent warping due to cure shrinkage.
[0030] After the HC resin composition of the present invention is applied, it is cured using an ultraviolet irradiator. Examples of light sources for irradiating ultraviolet rays include low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, carbon arc lamps, xenon lamps, metal halide lamps, electrodeless ultraviolet lamps, and LED lamps, and the curing conditions are 100 mW / cm. 2 ~3000mW / cm 2 The irradiation intensity is 50 to 2,000 mJ / cm2 as the cumulative light quantity. 2The irradiation atmosphere may be air or an inert gas such as nitrogen or argon, but curing in an inert gas is preferred to prevent curing inhibition due to oxygen.
[0031] The present invention will be described in detail below with reference to examples and comparative examples, but these are merely illustrative examples and are not intended to be limiting. The amounts blended are in parts by weight, and unless otherwise indicated, measurements were taken at room temperature of 25°C and relative humidity of 65%.
[0032] Example 1 The HC resin composition of Example 1 was prepared by using M-460 (product name: Toagosei Co., Ltd., EO-modified (modification number 4) DGTA) as (A), VEEA (product name: Nippon Shokubai Co., Ltd., 2-(2-vinyloxyethoxy)ethyl acrylate) as (B), and Omnirad127 (product name: IGM Resins, α-hydroxyphenone type) as (C) in the formulation shown in Table 1 and stirring until uniformly dissolved.
[0033] Examples 2 to 8 The HC resin compositions of Examples 2 to 8 were prepared by using A-DPH-12E (product name: Shin-Nakamura Chemical Co., Ltd., EO-modified (modification number 12) DPHA) and SR454NS (product name: SARTOMER, EO-modified (modification number 3) TMPTA) as the (A) and M-940 (product name: Toagosei Co., Ltd., DPHA) as a reactive diluent in the formulation shown in Table 1 and stirring until uniformly dissolved.
[0034] Comparative Examples 1 to 5 In addition to the materials used in the examples, A-TMMT (product name: pentaerythritol tetraacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.) and M-309 (product name: TMPTA, manufactured by Toagosei Co., Ltd.) were used as monomers in place of (A), and the HC resin compositions of Comparative Examples 1 to 5 were prepared by stirring until uniformly dissolved in the formulation shown in Table 2.
[0035] Table 1 JPEG2025021498000001.jpg75146
[0036] Table 2 JPEG2025021498000002.jpg103150
[0037] The evaluation method was as follows.
[0038] Preparation of HC film for evaluation The HC resin composition prepared above was used to coat A4300 (product name: Toyobo Co., Ltd., PET film with a thickness of 50 μm) so that the dry film thickness was 4 μm, and ultraviolet light was irradiated using an electrodeless UV lamp manufactured by FUSION Co., Ltd. with an H bulb at an output of 600 mW / cm2 and an accumulated light amount of 150 mJ / cm2 (365 nm) to prepare an HC film for evaluation.
[0039] Viscosity: Using a Brookfield viscometer TVB-10 manufactured by Toki Sangyo Co., Ltd., the viscosity was measured after 1 minute at 25±1° C., rotor No. M1, and rotation speed of 60 rpm.
[0040] Coating ability: When preparing the HC film for evaluation as described above, the appearance was visually inspected. A mark of ◎ was given if there were no coating unevenness or coating streaks due to high viscosity, a mark of ◯ was given if the leveling ability was almost good but not perfect, a mark of △ was given if the leveling ability was not perfect and some coating streaks were visible, and a mark of × was given if the coating streaks were clearly visible and the leveling ability was poor.
[0041] Curability: When preparing the HC film for evaluation as described above, the tackiness of the coating surface immediately after UV curing was checked. If the coating was cured and had no tackiness, it was marked as ◯, and if the coating was tacky but not cured, it was marked as ×.
[0042] Abrasion resistance: Using an abrasion tester manufactured by Toyo Seiki Co., Ltd., a load was placed on steel wool #0000 with a contact area of 25 mm in diameter, and the material was moved back and forth 10 times at a speed of 30 times per minute. The HC film was then blackened and visually observed. When the load was more than 300 g and no scratches were observed, it was evaluated as ◎, when it was 200 to 300 g, it was ○, and when it was less than 200 g, it was evaluated as ×.
[0043] Bending resistance: Using a cylindrical mandrel tester PF-5710 manufactured by Byk-Gardner, the above HC film was cut to 120 mm x 30 mm and bent once at 180° (outward bending) to measure the minimum bending radius (Rmm) at which cracks did not occur. 1R was marked as ◎, 1.5R as ◯, and more than 1.5R as ×.
[0044] Evaluation results Table 3 JPEG2025021498000003.jpg74150
[0045] Table 4 JPEG2025021498000004.jpg101150
[0046] Each of the formulations in the Examples was satisfactory with no problems in all respects, including viscosity, coatability, curability, scratch resistance and flexibility.
[0047] On the other hand, Comparative Example 1, in which the blending amount of (B) exceeded the upper limit, exhibited poor scratch resistance, and Comparative Example 2, in which the blending amount of (B) was below the lower limit, exhibited poor coatability. In addition, Comparative Examples 3 and 4, in which a non-EO-modified monomer was used instead of (A), exhibited poor flexibility, and Comparative Example 5 exhibited poor scratch resistance, and none of the blends were suitable for the present invention.
Claims
1. A solventless hard coat resin composition comprising: an alkylene oxide-modified polyfunctional (meth)acrylate (A); a vinyl ether group-containing (meth)acrylate (B); and a photopolymerization initiator (C), the amount of (B) being 15 to 70% by weight based on the total solid content.
2. 2. The solventless hard coat resin composition according to claim 1, wherein (A) comprises a derivative of a (meth)acrylate selected from the group consisting of glycerin poly(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol poly(meth)acrylate.
3. 2. The solventless hard coat resin composition according to claim 1, wherein said (B) is a monofunctional (meth)acrylate containing one vinyl ether group in the molecule.
4. 4. An optical laminate comprising a plastic substrate and a cured layer of the solventless hard coat resin composition according to claim 1 formed on at least one surface of the substrate.
Citation Information
Patent Citations
Composition for hard coat
JP2012107225A
Active energy ray-curable hard coat composition
JP2013136737A
Solvent-free curable composition for hard coat and cured film thereof
WO2009050957A1